2021
DOI: 10.1111/aec.13091
|View full text |Cite
|
Sign up to set email alerts
|

The ecological costs and benefits of a feral cat poison‐baiting programme for protection of reintroduced populations of the western quoll and brushtail possum

Abstract: Conservation practitioners implement management interventions for the protection of threatened species, but the benefits are rarely measured. We investigated the efficacy of aerial poison baiting for feral cats, a species identified as a threat to reintroduced populations of two Australian mammals. We measured individual survival, short‐term changes in activity and longer term population trajectories in cats and reintroduced western quolls and brushtail possums before and after annual baiting events. Between 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Notably, in one case, a dingo was observed to have consumed an entire kangaroo carcass within a 24-h period. The relative absence of dingoes at carcass sites, along with similarly low rates of scavenging by red foxes and feral cats, is likely to have especially influenced the use of carcasses by brushtail possums who regularly feature in the diets of these three predators (Jones and Coman 1981;Newsome et al 1983;Dickman 1996;Vernes et al 2001;Kinnear et al 2002;Brook and Kutt 2011;Pascoe et al 2012;McComb et al 2018;Fleming et al 2021;Moseby et al 2021). Further still, recent findings in Australia have demonstrated that ravens, in the absence of top scavengers, scavenged across all four seasons and not only during the cooler months when other resources were low (Fielding et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in one case, a dingo was observed to have consumed an entire kangaroo carcass within a 24-h period. The relative absence of dingoes at carcass sites, along with similarly low rates of scavenging by red foxes and feral cats, is likely to have especially influenced the use of carcasses by brushtail possums who regularly feature in the diets of these three predators (Jones and Coman 1981;Newsome et al 1983;Dickman 1996;Vernes et al 2001;Kinnear et al 2002;Brook and Kutt 2011;Pascoe et al 2012;McComb et al 2018;Fleming et al 2021;Moseby et al 2021). Further still, recent findings in Australia have demonstrated that ravens, in the absence of top scavengers, scavenged across all four seasons and not only during the cooler months when other resources were low (Fielding et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…C Image metadata were extracted using the package 'CamtrapR' in R (Niedballa et al 2016;R Core Team 2020). Consistent with previous study in the area (Moseby et al 2021a), and similar study on burrows (Dawson et al 2019), captures of animals on camera were counted as an independent capture event if they were separated by 10 min or more. Multiple images of the same species taken within a 10-min period were counted as one capture event or visitation of that species to the camera.…”
Section: Camera Trappingmentioning
confidence: 99%
“…In this case, having a long-term dataset, which may in fact not be long at all in these arid systems, did not seem to compensate for the lack of a control site. Several authors have recommended that long-term monitoring, through a range of seasonal conditions be undertaken to improve our understanding of ecosystem change (Read 2002;Kraaij and Milton 2006;Pedler et al 2016;Moseby et al 2021;Piazza et al 2021). Given that stray stock continue to graze the Park, correlative analysis is limited, and that further years of study will only reduce the uncertainty slowly, it would be more useful to establish a control site on a neighbouring cattle station to better evaluate trends in habitat condition and the kowari population.…”
Section: The Value Of Long-term Datasets and Control Sitesmentioning
confidence: 99%